2008
DOI: 10.1113/jphysiol.2007.143057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of passive heating on central blood volume and ventricular dimensions in humans

Abstract: Mixed findings regarding the effects of whole-body heat stress on central blood volume have been reported. This study evaluated the hypothesis that heat stress reduces central blood volume and alters blood volume distribution. Ten healthy experimental and seven healthy time control (i.e. non-heat stressed) subjects participated in this protocol. Changes in regional blood volume during heat stress and time control were estimated using technetium-99m labelled autologous red blood cells and gamma camera imaging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
176
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(192 citation statements)
references
References 19 publications
12
176
3
1
Order By: Relevance
“…11,12 It is well established that heat stress modified the blood distribution of Q to the systemic circulation by an increase in cutaneous blood flow for thermoregulation. 4,[13][14][15] Similar to systemic circulation, the contribution of Q to CBF may be altered by heat stress. In the previous study, we have demonstrated that blood distribution in the brain (posterior and anterior CBF) was altered by several physiologic conditions, i.e., dynamic exercise 7 and orthostatic stress.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 It is well established that heat stress modified the blood distribution of Q to the systemic circulation by an increase in cutaneous blood flow for thermoregulation. 4,[13][14][15] Similar to systemic circulation, the contribution of Q to CBF may be altered by heat stress. In the previous study, we have demonstrated that blood distribution in the brain (posterior and anterior CBF) was altered by several physiologic conditions, i.e., dynamic exercise 7 and orthostatic stress.…”
Section: Introductionmentioning
confidence: 99%
“…This displacement of blood away from the heart creates a regulatory problem, decreasing central blood volume, ventricular filling pressure, stroke volume and subsequently mean arterial blood pressure (MAP) (Crandall et al 2008). Mean arterial pressure can be maintained by increasing heart rate (HR) and myocardial contractility (and thus, Á Q), increasing peripheral vascular resistance, and limiting venous pooling (Wilson et al 2007;Crandall et al 2008). However, sustaining a higher HR under prolonged stress increases the risk of cardiac events, particularly in the elderly (Donaldson et al 2003).…”
mentioning
confidence: 99%
“…Vasodilation of cutaneous vessels decreases total peripheral resistance (TPR) and increases cutaneous vascular conductance (CVC). These changes reduce central blood volume (CBV) and lead to a 2 -6 mm Hg drop in central venous pressure (CVP) and a 5 -10 mm Hg decline in MAP [14,69]. Therefore, in response to large increases in SBF, cardiac output (Q), which is the product of stroke volume (SV) and heart rate (HR), must increase and vascular conductance in other vascular beds must decrease to prevent a decline in MAP and oxygen delivery to the brain [61,67,69].…”
Section: Blood Pressure Regulation During Heat Stressmentioning
confidence: 99%
“…High internal body temperature (T c ) can have profound effects on the cardiovascular system during resting conditions [12,14,67]. Furthermore, when T c is elevated above normal levels during exercise, the demands placed on the cardiovascular system can be extreme.…”
Section: Introductionmentioning
confidence: 99%